Molecular identification of Theileria and Babesia in ticks collected from sheep and goats in the Black Sea region of Turkey - Aydin, Mehmet Fatih; Aktas, Munir; Dumanli, Nazir (Springer, 2015)
A molecular survey was undertaken in the Black Sea region of Turkey to determine the presence of Theileria and Babesia species of medical and veterinary importance. The ticks were removed from sheep and goats, pooled according to species and locations, and analyzed by PCR-based reverse line blot (RLB) and sequencing. A total of 2241 ixodid ticks belonging to 5 genus and 12 species were collected and divided into 310 pools. Infection rates were calculated as the maximum likelihood estimation (MLE) with 95 % confidence intervals (CI). Of the 310 pools tested, 46 (14.83 %) were found to be infected with Theileria or Babesia species, and the overall MLE of the infection rate was calculated as 2.27 % (CI 1.67-2.99). The MLE of the infection rates were calculated as 0.691 % (CI 0.171-1.78) in Haemaphysalis parva, 1.47 % (CI 0.081-6.37) in Rhipicephalus sanguineus, 1.84 % (CI 0.101-7.87) in Ixodes ricinus, 2.86 % (CI 1.68-4.48) in Rhipicephalus turanicus, 5.57 % (CI 0.941-16.3) in Hyalomma marginatum, and 6.2 % (CI 4.02-9.02) in Rhipicephalus bursa. Pathogens identified in ticks included Theileria ovis, Babesia ovis, Babesia bigemina, and Babesia microti. Most tick pools were infected with a single pathogen. However, five pools displayed mixed infections with T. ovis and B. ovis. This study provides the first molecular evidence for the presence of B. microti in ticks in Turkey.
Keywords: Babesia; RLB; Theileria; Tick